An Investigation Of Implementation Of Speaking Strategies In English Class Room: Gore Secondary School In Focus - Teshome Habtemariam (My University, 2017)
The main objective of the study was to investigate the Implementation of Speaking Strategies in English Classroom. The research mainly focused on the role of teachers in teaching speaking skill in the classroom, strategies used by the teachers to implement speaking skills, speaking activities that are used in the classroom and the students’ role in making use of strategies in the classroom for speaking skills. To this end, the study employed both quantitative and qualitative data gathering tools. The participant of the study were 450 grade 9 students and 4 English teachers from Gore secondary school. In order to collect relevant data, the study utilized three types of data collection instruments namely: questionnaire, interview and classroom observations. The questionnaire was the main data-gathering tool. While the interview and the classroom observations used to supplement and triangulate the data obtained through the questionnaire. To analyze the quantitative data, frequency and percentage have been used, whereas the qualitative data were analyzed using narration. The findings of the study revealed that the teachers are not aware of speaking strategies to teach speaking skills. Moreover, the teachers do not encourage their students to practice speaking. Furthermore, the activities for teaching speaking skill proved not suitable for speaking. Finally, recommendations were forwarded based on the major findings of the study in order to implement speaking strategies.
Gore Secondary School In Focus